Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berdasarkan Metode Graphic Rating Scale Pada Rumah Sakit PHC Surabaya - Rahmadi, Dimas Agung; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Primasatya Husada Citra (PHC) Surabaya Hospital is a subsidiary from PT. Pelabuhan Indonesia III. Existing problem in PHC Surabaya arise when assessing the performance of the employee. Approximately 15% of the assessment field are empty and other 15% are miscalculation. That were a sign that the evaluator does not take the assestment seriously and the evaluator just use a calculator to calculated the result of the assestment. That can cause a mistake on the assessment. Also, SDM is having a trouble to do the assestment over 800 employees of the Hospital and record the assessment. It takes very long time until the end of the assessment period still haven’t finish yet and the risk of making mistakes the assessment record is also big because the assessment still using a paper, SDM must record the assessment manually. The offered solution from all the problem is make a determination of employees performances appraisal aplication with graphic rating scales method, which can calculating the assessment correctly. The aplication can help the SDM to do performance appraisal according with period and record all assessment result precisely. Correctly performance assesment result can help the management to do the decision-making and make a correct treatment for the employee.